Chitosan-Based Non-viral Gene and Drug Delivery Systems for Brain Cancer - Lara-Velazquez, Montserrat; Alkharboosh, Rawan; Norton, Emily S.; Ramirez-Loera, Cristopher; Freeman, William D.; Guerrero-Cazares, Hugo; Forte, Antonio J.; Quiñones-Hinojosa, Alfredo; Sarabia-Estrada, Rachel (Frontiers in Neurology, 2020)
Central nervous system (CNS) tumors are a leading source of morbidity and mortality worldwide. Today, different strategies have been developed to allow targeted and controlled drug delivery into the brain. Gene therapy is a system based on the modification of patient’s cells through the introduction of genetic material to exert a specific action. Administration of the foreign genetic material can be done through viral-mediated delivery or non-viral delivery via physical or mechanical systems. For brain cancer specifically, gene therapy can overcome the actual challenge of blood brain barrier penetration, the main reason for therapeutic failure. Chitosan, a natural based biodegradable polymer obtained from the exoskeleton of crustaceans such as crab, shrimp, and lobster, has been used as a delivery vehicle in several non-viral modification strategies. This cationic polysaccharide is highly suitable for gene delivery mainly due to its chemical properties, its non-toxic nature, its capacity to protect nucleic acids through the formation of complexes with the genetic material, and its ease of degradation in organic environments. Recent evidence supports the use of chitosan as an alternative gene delivery system for cancer treatment. This review will describe multiple studies highlighting the advantages and challenges of chitosan-based delivery structures for the treatment of brain tumors. Furthermore, this review will provide insight on the translational potential of various chitosan based-strategies in current clinical cancer studies. Specifically, chitosan-based nanostructures including nanocapsules, nanospheres, solid-gel formulations and nanoemulsions, also microshperes and micelles will be evaluated.